Cerebral Revascularization for the Management of Symptomatic Pure Arterial Malformations - Lu, Xiaocheng; Fang, Xinggen; Huang, Yabo; Zhou, Peng; Wang, Zhong; Brinjikji, Waleed; Chen, Gang (Frontiers in Neurology, 2021)
Background: Pure arterial malformations (PAMs) are extremely rare abnormalities defined as dilated, overlapping, and tortuous arteries with a coil-like appearance in the absence of venous components. Over the last half century, only seven published reports have described cases of patients with PAMs who received treatment. Methods: Here, we report two cases of women with PAMs who received surgical treatment, and we present a systematic review of the literature. We searched the PubMed, Embase, Web of Science, and Medline databases (up until October 1, 2021) for relevant publications. We performed independent-sample t-tests and Fisher's exact tests to compare continuous and categorical characteristics among the available cases. Results: Our first patient was a 43-year-old woman with PAM of the left internal carotid artery (ICA), who received an ICA-radial artery (RA)-M2 bypass. Post-operative digital subtraction angiography (DSA) revealed the disappearance of the left ICA PAM without ischemic events during follow-up. The second patient was a 53-year-old woman with PAMs of the right ICA and posterior cerebral artery. The P1 lesion was treated by proximal occlusion combined with a superficial temporal artery-P2 bypass. During the 12-month follow-up period, the size of the PAMs decreased significantly as indicated by the post-operative DSA showing the absence of hemorrhages. Our systematic review, which includes 56 PAMs, shows that the reported PAMs were more common in the anterior circulation (33/56, 58.9%) than in the posterior circulation (11/56, 19.7%). Bilateral PAMs were more likely to affect bilateral anterior cerebral arteries (ACA) (ACAbilateral vs. ACAunilateral: 63.6 vs. 26.2%, p = 0.02). In addition, PAMs involving the anterior circulation were likely to affect multiple arteries (anteriormulti vs. posteriormulti: 30.3 vs. 0%, p = 0.038). Conclusion: We found very few reports on treated PAMs; further studies with large sample sizes and long follow-up periods are required to explore the appropriate treatment strategy for PAMs.